Modeling riparian species occurrence from historical surveys to guide restoration planning in northwestern USA. Issue 5 (16th May 2021) - Beechie, Timothy J.; Stefankiv, Oleksandr; Bond, Morgan; Pollock, Michael
Abstract: Successful restoration of riparian habitats and functions depends in part on selection of plant species that are suited to local geomorphic and climatic conditions, which often relies on contemporary reference sites to characterize target riparian vegetation communities. In heavily modified landscapes, a lack of undisturbed sites hinders the description of reference conditions to help guide planning efforts. In lieu of contemporary reference sites, we used historical Public Land Survey data from the late 1800s and early 1900s to document historical streamside vegetation at 1685 sites distributed throughout the Columbia River basin. We used those data to construct a random forest classification model using climatic and geomorphic variables to predict the probability of occurrence of riparian vegetation groups (conifer, deciduous, shrub, and willow) and individual taxa (fir, pine, cedar, cottonwood, alder, sagebrush) for all stream reaches with bankfull width >6 m in the interior Columbia River basin. The most common predictor variables included in the best models for vegetation groups or individual taxa were mean annual precipitation, minimum temperature, elevation, and bankfull width. For some taxa, temperature range and floodplain width were also important predictors. The probability maps indicate that riparian zones were likely dominated by willow species in semi‐desert regions and by conifer species in the humid mountain regions. Deciduous species dominated riparian areas in transition zones between conifer forests and semi‐deserts. Species distributions suggest that streams in the semi‐deserts were likely characterized by little shade and low wood abundance, whereas streams in the humid mountains would have been more heavily shaded with high wood abundance. The transitional deciduous areas were likely shaded with moderate wood abundance. Historical trends in air temperature and precipitation suggest relatively small changes in climate since the time of the surveys, indicating that current species ranges are likely similar to historical species ranges. Hence, these maps can be used to help identify suitable taxonomic groups and expected riparian functions for riparian restoration in the Columbia River basin, with appropriate adjustments made to site‐specific restoration designs to account for model uncertainty, future climate change, or land use constraints.